LO37: Reducing hemolysis of coagulation blood samples in the emergency department. (May 2020) - Weatherby, H.; Woolner, V.; Chartier, L.; Casey, S.; Ong, C.; Gaylord, E.
Abstract : Background: Hemolysis of blood samples is the leading cause of specimen rejection from hospital laboratories. It contributes to delays in patient care and disposition decisions. Coagulation tests (prothrombin time/international normalized ratio [PT/INR] and activated partial thromboplastin time [aPTT]) are especially problematic for hemolysis in our academic hospital, with at least one sample rejected daily from the emergency department (ED). Aim Statement: We aimed to decrease the monthly rate of hemolyzed coagulation blood samples sent from the ED from a rate of 2.9% (53/1, 857) to the best practice benchmark of less than 2% by September 1st, 2019. Measures & Design: Our outcome measure was the rate of hemolyzed coagulation blood samples. Our process measure was the rate of coagulation blood tests sent per 100 ED visits. Our balancing measure was the number of incident reports by clinicians when expected coagulation testing did not occur. We used monthly data for our Statistical Process Control (SPC) charts, as well as Chi square and Mann-Whitney U tests for our before-and-after evaluation. Using the Model for Improvement to develop our project's framework, we used direct observation, broad stakeholder engagement, and process mapping to identify root causes. We enlisted nursing champions to develop our Plan-Do-Study-Act (PDSA) cycles/interventions: 1) educating nurses on hemolysis and coagulation testing; 2) redesigning the peripheral intravenous and blood work supply carts to encourage best practice; and 3) removing PT/INR and aPTT from automatic inclusion in our electronic chest pain bloodwork panel. Evaluation/Results: The average rate of hemolysis remained unchanged from baseline (2.9%, p = 0.83). The average rate of coagulation testing sent per 100 ED visits decreased from 41.5 to 28.8 (absolute decrease 12.7 per 100, p < 0.05), avoiding $4, 277 in monthly laboratory costs. The SPC chart of our process measure showed special cause variation with greater than eight points below the centerline. Discussion/Impact: Our project reduced coagulation testing, without changing hemolysis rates. Buy-in from frontline nurses was integral to the project's early success, prior to implementing our electronic approach – a solution ranked higher on the hierarchy of intervention effectiveness – to help sustainability. This resource stewardship project will now be spread to a nearby institution by utilizing similar approaches.